An Assistive Computer Technology Implementation Program for Students with Cerebral Palsy - Gerusa Ferreira Lourenço; Enicéia Mendes (Universidade de Lisboa, 2022)
Assistive technology devices can help students with cerebral palsy to perform everyday tasks in school more efficiently and independently. However, the implementation of such a system is a complex process and an essential element of its successful application is the involvement of a skilled and experienced team of professionals. The aim of this study was to implement and evaluate the effects of an in-service assistive technology training program for school professionals-which was developed to facilitate the learning process of students with cerebral palsy in a special school in a city located within São Paulo State (Brazil)-using a collaborative research approach. Data were collected from open-ended response questionnaires, focus groups, videotapes, and field notes. The results indicated that such a collaborative program can effectively enable teachers, school staff members and students to use these types of assistive technology devices, and additionally, that the collaborative nature of the project was of overriding importance.